Taxonomic revision of Salvia subgenus Calosphace section Scorodoniae (Lamiaceae), endemic to Mexico - Olvera Mendoza, Edgar Ismael; Bedolla García, Brenda Y.; Lara Cabrera, Sabina I. (Instituto de Ecología, A.C., 2017)
Background and Aims: The Mexican section Scorodoniae, of Salvia subgenus Calosphace is reviewed. Contributing to the efforts to know the Mexican flora several sections sensu Epling are being reviewed by different authors, including diagnostic characters and species descriptions. Even with Turner’s short treatment of Salvia sect. Scorodoniae several species remained difficult to identify. The objective of this research was to diagnose Scorodoniae, provide species descriptions, synonyms, type specimens, an identification key and distribution maps.Methods: Four hundred and sixty specimens of Salvia secc. Scorodoniae deposited at EBUM, ENCB, IEB, MEXU y UAMIZ were reviewed. Identification was made using several taxonomic treatments, protocols and type specimens.Key results: Salvia tepicensis is a synonym of S. aequidistans. Salvia dugesii and S. gonzalezii are recognized as species and no longer treated as synonyms of S. melissodora y S. pannosa respectively. Salvia fruticulosa previously classified in sect. Tomentellae is now placed in Scorodoniae.Conclusions: Sixteen species of Salvia section Scorodoniae are recognized, characterized by the deltoid, ovate to ovate-lanceolate or elliptic-lanceolate lamina, with bullate-rugose upper surface, and their small flowers.